IBN MISKAWAIH'S THOUGHTS ON MORAL EDUCATION AND ITS RELEVANCE AT UNIVERSITAS MUHAMMADIYAH SURAKARTA - Hartono; Imron Rosyadi (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this study is to analyze Ibn Miskawaih's thoughts on morals and their relevance at the University of Muhammadiyah Surakarta, where moral education in this era is very important, along with the times, technological developments, generations and models of social interaction. When the younger generation (students) easily get information through gadgets, the internet, and social media, they are increasingly unable to control themselves. The long-term result of this is promiscuity, perversion and moral degradation. In line with this, education in schools still prioritizes science in addition to moral cultivation, so education has a decline in moral quality. Long before the development of the times and technology, Islamic scholars and thinkers formulated the concept of moral education they might think far away about its contribution and relevance in the current era. The method used is qualitative descriptive, with content analysis, phenomenological, philosophical, and historical approaches. The results of the study concluded that Ibn Miskawaih was one of the thinkers in the field of moral education. Aspects of his thought include human potential al-nafs al-bahimiyyat, al-nafs al-sabuiyyat, al-nafs al-nathiqah. The goal of moral education is that mental attitudes encourage good deeds spontaneously. Educational functions: cultivation of noble morals, humanizing humans, cultivation of shame, moral education materials, namely applicable moral laws, educational methods namely tabi'i, advice, threats, flattery and praise. This concept is relevant to moral education at the University of Muhammadiyah Surakarta, namely by instilling tawhid education (prioritizing God the Creator), returning to the Qur'an and Hadith as guidelines and references, routinely worshipping the sunnah, teaching the concept of a just leader, upholding the truth, Islamic organizations (IMM, MPQ and AIK Mentoring), the concept of benefit for society, the concept of the world-hereafter and Islam-science for human piety.